STRATEGIES FOR MEETING THE STANDARDS OF EDUCATORS AND EDUCATION PERSONNEL IN ISLAMIC BOARDING SCHOOL-BASED MADRASAS - Nursyamsiah Nursyamsiah; Wahyudin Nur Nasution; Candra Wijaya (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to analyze the strategy of meeting the standards of educators and education personnel in the leading integrated modern Islamic boarding school Darul Mursyid, South Tapanuli Regency. The research method used in this research is using qualitative research with a descriptive analysis approach. The results of this study conclude that (1) the Islamic boarding school determines a minimum qualification of S-1 for educators and is competent according to the field of expertise; (2) the pesantren implements training activities, supervision, placement according to the field of expertise, and regular assessment of educators; (3) the pesantren takes time for educators to be able to attend training and develop their potential, as well as opportunities for comparative stunies; (4) equalizing the perception of educators that learning orientation is to create Islamic, independent, moral, intellectual and professional students; and (5) the pesantren creates a sustainable pattern for educators and education personnel in planning, procurement, coaching and development, promotion, termination/termination of work contracts, and evaluation equally for every educator and education staff.